2003
DOI: 10.1001/archotol.129.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Salvage Total Laryngectomy Following Organ Preservation Therapy

Abstract: Laryngectomy following organ preservation treatment is associated with acceptable morbidity. Perioperative mortality is low but up to one third of patients will develop a pharyngocutaneous fistula. Local-regional control is excellent for this group of patients. Survival following salvage TL was not influenced by the initial organ preservation treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
429
4
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 486 publications
(468 citation statements)
references
References 17 publications
31
429
4
4
Order By: Relevance
“…In other studies [18,[25][26][27][28] mean time of restoration a normal feeding was 25 days and in Pellini's study was in less than 1 month for 61.5 % of patients [22]. The time of removal of the feeding tube ranged in literature from 10-96 days [28] to 12-90 days [18], in our study was 4-230 days.…”
Section: Complications and Functional Resultssupporting
confidence: 38%
See 1 more Smart Citation
“…In other studies [18,[25][26][27][28] mean time of restoration a normal feeding was 25 days and in Pellini's study was in less than 1 month for 61.5 % of patients [22]. The time of removal of the feeding tube ranged in literature from 10-96 days [28] to 12-90 days [18], in our study was 4-230 days.…”
Section: Complications and Functional Resultssupporting
confidence: 38%
“…The incidence of late complications as stoma stenosis is estimated in literature about 9 % [5] while in our case study was 4 % and they all required surgical reintervention. The most common complication is pharyngocutaneous fistula, which had an incidence of 32 % in our study, 11.9 % in Ganly's and 30 % in Weber's [25]. The rate of pharyngocutaneous fistula following STL in irradiated patients is higher than that after total laryngectomy as primary treatment (from 68 to 8.69 % [30][31][32]).…”
Section: Complications and Functional Resultsmentioning
confidence: 62%
“…Higher survival rates for laryngeal cancer were confirmed after primary laryngectomy, and organ preservation strategy resulted in decrease of global survival for laryngeal cancer from 66% to 63% in the last years [1,4]. Radiotherapy for laryngeal cancer produces more frequent fistulas especially when bigger fields and doses were used.…”
Section: Discussionmentioning
confidence: 99%
“…Also, salvage surgery is accompanied by higher complication rate, and worse survival rate [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The risk of developing pharyngocutaneous fistulas is increased if radiation therapy has taken place previously [132], [133]. Data of the Radiation Therapy Oncology Group 91-11 and investigations from Japan reveal wound complication rates of 46-59%, with rates for pharyngocutaneous fistulas of 15-38% [134], [135]. Fung et al showed that reconstruction with microvascular free flaps in salvage surgery does avoid more extensive wound healing disorders [136].…”
Section: Specificities Of Wound Healing In Recurrences After Radio(chmentioning
confidence: 99%